Synthesis and Application of Some Sulfonamides as Bacteriostatic Antibiotics - Khazaei, Ardeshir; Fatemeh Sadeghian, Sayid; Hesami, Shohreh; Amini Manesh, Abbas (Asian Journal of Chemistry, 2010)
The new sulfonamides; N(1-amino phenyl)-4-amino benzene sulfonamide, N(1-amino-4-nitro phenyl)-4-aminobenzenesulfonamide (3) were synthesized and bacteriostatic effects were studied by two methods: disc diffusion and serial dilution on three bacteria (E. coli, B. cereus and S. aureus). Addition of electronegative groups such as nitro showed that bacteriostatic effects were increased.